A Sociolinguistics Study Of Erotic Register Used In Jakarta Undercover 3 Novel By Moammar Emka - Wibawanti, Frita Dwi, Drs. H. Maryadi, MA, Dra. Siti Zuhriah, M. Hum (2013)
This study is about a sociolinguistic study of erotic in Jakarta Undercover 3 novel. The objectives of the study are conducted (1) to identify the grammatical forms of erotic register in the novel, (2) to identify the meaning of erotic register that use in Jakarta Undercover 3 novel and (3) to clarify the motive of using the register in the novel. The object of the study is the register of erotic expression used in Jakarta Undercover 3 novel. It used a sociolinguistic study. This research is a descriptive qualitative research. The type of data in this study is a text that consists of words, phrases and sentences. The data source is Jakarta Undercover 3 novel by Moammara Emka. In collecting the data, the writer looks for Jakarta Undercover 3 novel, read Jakarta Undercover 3 novel, provides numbering on each paragraph, writes down the erotic register words and phrases and gives code of the data. In analyzing the data, the writer analyze the form of the register by referring by the grammatical forms, analyze the meaning of register by referring to the Larson's theory and draw conclusion/suggestion based on the data analysis. Based on the analysis, the researcher finds the data (1) based on the grammatical form (4 data of noun, 2 data of verb, a datum of preposition, 5 data of compound, 2 data of abbreviation, 20 data of noun phrase, a datum of adjective phrase and a datum verb phrase). (2) Based on the meaning, the writer finds 33 data of contextual meaning and 3 data of lexical meaning.(3) Based on the motives, the writer finds 25 data of need filling motives and 11 data of prestige filling motive.